2021
DOI: 10.1021/acssuschemeng.1c04735
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Enhancement of Oxygen Evolution in CoNi@C Nanosheets

Abstract: Recently, electron spin manipulation is being considered as a potential technique to promote oxygen electrocatalytic reactions; however, the specific spin-polarized kinetics remain unclear. In this work, a series of magnetic electrocatalysts, CoNi@C, was successfully prepared. The catalysts exhibited room-temperature ferromagnetism with a high saturation magnetization (over 50 emu/g). An external magnetic field significantly improved the catalytic activity for the oxygen evolution of the catalysts under alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…The R ct was fitted by a simple equivalent circuit (shown in the inset of Figure e). Similar variations of C dl and R ct with applying an external magnetic field have been reported in the literature, both experimentally and theoretically. Dunne and Coey concluded that the modification of both C dl and R ct with applied magnetic field is related to the spin-dependent kinetics of electrochemical redox reactions at the working electrode/electrolyte interface . Therefore, our increased C dl and decreased R ct suggest that the long-ranged FM ordering is achieved in CrTe 3 , which is in line with magnetic measurements of the observed room-temperature hysteresis loop and exchange bias, and thus promotes spin-dependent kinetics and rapid charge transfer for improving OER performance.…”
supporting
confidence: 89%
“…The R ct was fitted by a simple equivalent circuit (shown in the inset of Figure e). Similar variations of C dl and R ct with applying an external magnetic field have been reported in the literature, both experimentally and theoretically. Dunne and Coey concluded that the modification of both C dl and R ct with applied magnetic field is related to the spin-dependent kinetics of electrochemical redox reactions at the working electrode/electrolyte interface . Therefore, our increased C dl and decreased R ct suggest that the long-ranged FM ordering is achieved in CrTe 3 , which is in line with magnetic measurements of the observed room-temperature hysteresis loop and exchange bias, and thus promotes spin-dependent kinetics and rapid charge transfer for improving OER performance.…”
supporting
confidence: 89%
“…In addition, the weak magnetism produced by point defects and spin polarization can stimulate the spin state jump of Cu, which generates more unpaired electrons in the d orbitals of Cu . When oxygen enters the coating, overlap occurs between the Cu 3d and O 2p orbitals, and the transition metal Cu in Cu-HAP rapidly exchanges spin electrons with the adsorbed oxygen through spin polarization to facilitate the capture of oxygen in the corrosion reaction (Figure e), and this exchange of spin electrons is similar to ferromagnetic exchange . The reaction process is the protonation of oxygen adsorbed water.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the improvement of water splitting by the application of a magnetic field has attracted interest [171][172][173][174][175]. Numerous studies report an increase of the measured current when a magnetic field is applied to the electrodes.…”
Section: Overview Of Experimental Observations Of Magnetically Induce...mentioning
confidence: 99%